Transport stress induces heart damage in newly hatched chicks via blocking the cytoprotective heat shock response and augmenting nitric oxide production1. (11th July 2018) - Sun, F; Zuo, Y-Z; Ge, J; Xia, J; Li, X-N; Lin, J; Zhang, C; Xu, H-L; Li, J-L
Abstract: Transport stress affects the animal's metabolism and psychological state. As a pro-survival pathway, the heat shock response (HSR ) protects healthy cells from stressors. However, it is unclear whether the HSR plays a role in transport stress-induced heart damage. To evaluate the effects of transport stress on heart damage and HSR protection, newly hatched chicks were treated with transport stress for 2 h, 4 h and 8 h. Transport stress caused decreases in body weight and increases in serum creatine kinase (CK ) activity, nitric oxide (NO ) content in heart tissue, cardiac nitric oxide syntheses (NOS ) activity and NOS isoforms transcription. The mRNA expression of heat shock factors (HSFs, including HSF1–3) and heat shock proteins ( HSPs, including HSP25, HSP40, HSP47, HSP60, HSP70, HSP90 and HSP110 ) in the heart of 2 h transport-treated chicks was upregulated. After 8 h of transport stress in chicks, the transcription levels of the same HSPs and HSF2 were reduced in the heart. It was also found that the changes in the HSP60, HSP70 and HSP90 protein levels had similar tendencies. These results suggested that transport stress augmented NO generation through enhancing the activity of NOS and the transcription of NOS isoforms. Therefore, this study provides new evidence that transport stress induces heart damage in the newly hatched chicks by blocking the cytoprotective HSR and augmenting NO production.